2020
DOI: 10.1177/1534734620939528
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Buruli Ulcer Patients Following Discharge in the Greater Accra Region of Ghana

Abstract: Buruli ulcer (BU) is one of the skin diseases that causes physical deformity, loss of function of the affected part, social stigmatization, and financial burden to individuals affected. Annually, an approximated 6000 cases of BU are reported worldwide especially from West Africa, Central Africa, and Asia. The aim of the study was to assess the experiences of BU patients in the Greater Accra Region of Ghana following discharge from the hospital. The study employed a qualitative descriptive phenomenological appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…These findings for active and past BU infection are in keeping with previous psychological studies in BUD, which showed symptoms of anxiety in pre-ulcer states in 66.7% and 61.5% of ulcer states for active infection [ 19 ], and 19.5% anxiety and 31.7% depression for past infection [ 20 ].The disabling, disfiguring, and stigmatizing conditions associated with most NTDs results in mental distress in affected persons, and may result in persisting social participation restrictions even among BUD patients with past infection [ 10 ]. It is therefore not surprising that BUD patients with past infection have previously expressed a need to continue to access holistic case, including counselling services [ 38 , 39 ]. Most BUD patients and caregivers showed signs of mental distress such as fear, sadness, nervousness as a result of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…These findings for active and past BU infection are in keeping with previous psychological studies in BUD, which showed symptoms of anxiety in pre-ulcer states in 66.7% and 61.5% of ulcer states for active infection [ 19 ], and 19.5% anxiety and 31.7% depression for past infection [ 20 ].The disabling, disfiguring, and stigmatizing conditions associated with most NTDs results in mental distress in affected persons, and may result in persisting social participation restrictions even among BUD patients with past infection [ 10 ]. It is therefore not surprising that BUD patients with past infection have previously expressed a need to continue to access holistic case, including counselling services [ 38 , 39 ]. Most BUD patients and caregivers showed signs of mental distress such as fear, sadness, nervousness as a result of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In Ghana, Menlah et al 14 have assessed the experience of patients with Buruli ulcers after hospital discharge. Onoyama et al 15 have identified the importance of psychological issues in terms of ulcer development among patients with peripheral arterial disease.…”
Section: Editorialmentioning
confidence: 99%